Solar Water Heater Hybrid with Electric - ดูมีแด คอรีเยาะ; สือยุ ซูไรดา; กาซอ ซุลกิพลี (YRU Journal of Science and Technology, 2017)
This research aims to design and build a solar water heater electrical joint. To reduce the use of electricity generated from fossil fuels by electric water heater. The water heater Solar power works by using the natural circulation (Thermosyphons). The research found that design and build a solar water heater electrical joint. Consist of two parts: the solar panels. And hot water tanks The solar panels measures 70x95 cm with a glass lid. The inside of the box covered with insulation. water tank and Hot a 20 liter bucket of water beside the hole to install pipelines to and from the solar panel and another hole has been made for installing a water tap for using hot water. Testing water heater Solar electricity between 09.00 AM-04.00 PM found that solar water heater using solar panels. The internal temperature of solar panels is estimated at 70°C ambient air temperature of 42°C average temperature of 86°C average radiation absorber plate which is testing solar water heater using solar panels. Water temperature before entering the solar panels is estimated at 43°C temperature water from the solar panels is estimated at 53°C and hot water solar heating by a heater. The constant temperature of 60°C water temperature averages 56°C.